Rozwiąż równania . Dam naj

Odpowiedź:
a)[tex]\frac{1}{3} x-2=x+2[/tex] mnożymy *3
x-6=3x+6
x-3x=6+6
-2x=12 /:(-2)
x=-6
b)[tex]1-\frac{6}{7} x=\frac{4}{7}[/tex] mnożymy *7
7-6x=4
-6x=4-7
-6x=-3 /:(-6)
x=-3/-6
x=1/2
c)[tex]6(\frac{1}{4} x-2)=18[/tex] dzielimy przez 6
[tex]\frac{1}{4} x-2=3[/tex] mnożymy *4
x-8=12
x=12+8
x=20
d)[tex]\frac{x}{6} -\frac{1}{6} =1[/tex] mnożymy *6
x-1=6
x=6+1
x=7
e)[tex]-2(2x-1)=\frac{x}{3}[/tex] mnożymy *3
-6(2x-1)=x
-12x+6=x
-12x-x=-6
-13x=-6 /:(-13)
x=6/13
f)[tex]\frac{2}{5} (3-x)=-2[/tex] mnożymy *5
2(3-x)=-10 /:2
3-x=-5
-x=-5-3
x=8
Szczegółowe wyjaśnienie: